Advances in the assessment and study of suicide in late-life depression - Xu, Tianmei; Mao, Yanping; Wang, Ye; Zhang, Wenxuan; Cao, Haojun; Yu, Enyan (Frontiers in Psychiatry, 2025)
With the aging global population, the prevalence of late-life depression (LLD) has shown a significant upward trend. The prolonged presence of a depressed mood can lead to feelings of hopelessness and helplessness, thereby enhancing suicidal impulses and behaviors, which seriously affect the physical and mental health of the older population. However, current research on suicide has mainly focused on adolescents and adults, resulting in a lack of data on the identification, assessment, and intervention of suicide risk in LLD. LLD treatments include psychotherapy, medication, physiotherapy, and Internet intervention techniques. First-line antidepressants, in addition to cognitive behavioral therapy and repetitive transcranial magnetic stimulation, have been shown to be effective in patients with LLD. In this study, we review the research progress in the following three aspects: symptomatological characteristics, assessment tools, and treatment methods of suicide in LLD, providing a reference for clinical workers and researchers in clinical practice.